Dysfunctional Gaze and the Representation(s) of Women in Nuala Ní Chonchúir’s “As I Look” - Aláez Corral, Máximo (Complutense Journal of English Studies, 2019)
In this article I intend to analyse Nuala Ní Chonchúir’s short story “As I Look,” from her 2009 collection Nude, in relation to the concept of dysfunction, the representation of the nude female body, and the deconstruction of the conventional male gaze. My analysis will be backed up by a theoretical framework on objectification and will focus on dysfunction in the gaze and representation, and also in narration. I aim at highlighting dysfunction as an instrument to convey a new meaning around the visual/literary representation of women, a more positive and desirable connotation than the “functional” order of the visual norm.